An evaluation of mosquito repellents and essential plant oils as deterrents of Asian citrus psyllid. (June 2018) - Hall, David G.; Borovsky, Dov; Chauhan, Kamlesh R.; Shatters, Robert G.
Abstract: A study was conducted to evaluate mosquito repellents against Asian citrus psyllid (ACP), Diaphorina citri Kuwayama (Hemiptera: Liviidae) and to expand our knowledge of the potential of essential plant oils as deterrents of ACP infestations. The psyllid vectors a bacterium, ' Candidatus Liberibacter asiaticus, ' presumed causal agent of a serious disease of citrus, huanglongbing (also known as citrus greening disease). Twenty-two candidate deterrents were tested as 20% solutions in methanol using a laboratory assay. Adults were free to enter and settle in one of three vials containing orange jasmine flush, one vial treated with a candidate deterrent, one vial treated with water or one treated with methanol. Seven mosquito repellents (CisPMD, DEET, DHS220, Icaridin, IR-3535, S-220, and TransPMD) and four essential oils (citronella, lavender, lemon eucalyptus, and a commercial mixture of oils from orange, clove, cinnamon, eucalyptus and rosemary) reduced ACP infestations on flush in the vials. Following a 24-h assay period, an average of 75% (range 58–88%) fewer psyllids were found in vials treated with these deterrents as compared to the combined number found in the control vials. Greenhouse evaluations were conducted on phytotoxicity of 5 or 25% solutions of eight deterrents and on ACP colonization of citrus seedlings sprayed with these deterrents. Few ACP colonized seedlings sprayed with 25% solutions, but this was attributed to phytotoxicity. Infestations were reduced on seedlings treated with 5% solutions, but these reductions also were largely attributed to phytotoxicity. Although unsprayed seedlings were in close proximity, adults found these plants and laid relatively large numbers of eggs. While some of the mosquito repellents and essential plant oils deterred infestations, none was completely effective and 5–25% solutions were too phytotoxic to be feasible as direct plant sprays. These results indicated the deterrents as tested hold little potential as a major tactic for reducing ACP infestations in citrus. Alternative application approaches to avoid phytotoxicity could be explored, and individual constituents of the more promising essential plant oils could be investigated. Highlights: A lab study was conducted on candidate repellents for Asian citrus psyllid. Some candidates were moderately effective at a high application rate. A greenhouse evaluation showed the deterrents were phytotoxic to citrus seedlings. Few psyllids infested the seedlings, but this was attributed to phytotoxicity. The deterrents as tested hold little potential as a psyllid control tactic.